HUBUNGAN FAKTOR LINGKUNGAN FISIK RUMAH DENGAN KEJADIAN PNEUMONIA PADA BALITA (Studi Kasus di Wilayah Kerja Puskesmas Candi Lama Kecamatan Candisari Kota Semarang) - Esty Kurniasih; Suhartono Suhartono; Nurjazuli Nurjazulil (Jurnal Kesehatan Masyarakat (Undip), 2015)
Pneumonia is inflammation of lung parenchyma where asinus filled with liquid chafe into a wall alveoli and cavities interstisium. According to data Riskesdas 2013, the incident pneumonia highest found in age group 12-23 months with 21,7 per 1000 toddlers. In 2012, pneumonia most high rate occurrence there are in the work area Puskesmas Candi Lama Kecamatan Candisari with the number of people that is 620 toddlers from 4.150 toddlers. This research using the draft study case control. Samples are toddlers age 0-59 months. Large sample that is 36 toddlers group cases and 36 toddlers the control group. Analysis bivariat test using chi square. The result of bivariate analysis indicated that no relation the type of floor, wall type home, home residence density, a density of occupancy bedroom, home humidity levels, temperature, home ventilation, bedroom ventilation,and type of fuel to cook with pneumonia on toddlers and there was a correlation between natural lighting with pneumonia on toddlers with average of illuminance on a group of cases 66,19 lux and in the control group 102 lux. Natural light is risk factors scene pneumonia in toddlers in the work area Puskesmas Candi Lama, Kecamatan Candisari Kota Semarang.